"I Can't Go Far": Perceptions and Experiences of Heart Failure Patients Regarding Physical Activity: A Qualitative Study Using Semistructured Face-to-Face Interviews. (February 2022) - Charuel, Elodie; Bernard, Martial; Vaillant Roussel, Hélène; Cambon, Benoit; Ménini, Thibault; Lafarge, Elodie; Dutheil, Frédéric; Vorilhon, Philippe
Background: Participation in regular physical activity (RPA) is beneficial to the quality of life and life expectancy of patients with chronic heart failure (CHF). However, it is inadequate in many patients. Aims: To determine the factors that influence the practice of RPA in patients with CHF managed in general practice. Method: This was a qualitative study using semistructured, individual face-to-face interviews. Patients with CHF (New York Heart Association Stages 1–3) capable of participating in RPA were enrolled by their general practitioner. A longitudinal and transversal inductive thematic analysis was performed by two researchers. Results: Five themes emerged from the 19 interviews that were conducted. Poor knowledge of the disease and the benefits of participating in RPA, as well as the lack of motivation or enjoyment, in particular due to the absence of previous participation, were considered significant obstacles. Fear associated with CHF or other comorbidities was also an obstacle. Attendance at a rehabilitation center, family and social circles, and having a pet all appeared to be beneficial. Family and friends were important for motivating the patient to participate in an activity but could also be an obstacle when they were overprotective. Conclusion: This study helps highlight the difficulties for patients with CHF associated with participation in RPA. Despite the obstacles, there are enabling factors on which the general practitioner may rely to motivate their patients.